2021
DOI: 10.1021/acs.jmedchem.1c00767
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of TFF3 Reveals Novel Mechanistic Insights and a Gut-Stable Metabolite

Abstract: TFF3 regulates essential gastro- and neuroprotective functions, but its molecular mode of action remains poorly understood. Synthetic intractability and lack of reliable bioassays and validated receptors are bottlenecks for mechanistic and structure–activity relationship studies. Here, we report the chemical synthesis of TFF3 and its homodimer via native chemical ligation followed by oxidative folding. Correct folding was confirmed by NMR and circular dichroism, and TFF3 and its homodime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…It is however important to note that the environment and physiological conditions in the gut differ between species and individuals, depending on age, gender, health condition, and day time, and that such in vitro assays cannot fully reflect more complex, but also more variable human ex vivo and in vivo conditions . Our results, however, indicate that well-defined and reproducible USP-simulated gastrointestinal fluids provide translationally relevant and highly comparable peptide stability results that can foster preclinical drug development by identifying metabolic cleavage sites and offering valuable guidance for ligand improvements via medicinal chemistry strategies. , Optimized leads can then be moved on to more complex yet elaborate and ethically restricted models, such as ex vivo stability assays using freshly collected human/animal gut fluids ,,,,, or in vivo studies in surgically ligated rat intestine or phase-I clinical trials …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is however important to note that the environment and physiological conditions in the gut differ between species and individuals, depending on age, gender, health condition, and day time, and that such in vitro assays cannot fully reflect more complex, but also more variable human ex vivo and in vivo conditions . Our results, however, indicate that well-defined and reproducible USP-simulated gastrointestinal fluids provide translationally relevant and highly comparable peptide stability results that can foster preclinical drug development by identifying metabolic cleavage sites and offering valuable guidance for ligand improvements via medicinal chemistry strategies. , Optimized leads can then be moved on to more complex yet elaborate and ethically restricted models, such as ex vivo stability assays using freshly collected human/animal gut fluids ,,,,, or in vivo studies in surgically ligated rat intestine or phase-I clinical trials …”
Section: Discussionmentioning
confidence: 92%
“… 149 Our results, however, indicate that well-defined and reproducible USP-simulated gastrointestinal fluids provide translationally relevant and highly comparable peptide stability results that can foster preclinical drug development by identifying metabolic cleavage sites and offering valuable guidance for ligand improvements via medicinal chemistry strategies. 75 , 150 Optimized leads can then be moved on to more complex yet elaborate and ethically restricted models, such as ex vivo stability assays using freshly collected human/animal gut fluids 15 , 16 , 74 , 78 , 149 , 151 or in vivo studies in surgically ligated rat intestine or phase-I clinical trials. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Peptide synthesis was performed as previously described with small modifications (Braga Emidio et al, 2021). Peptides were synthesized on a Gyros Protein Technologies PurePep Chorus automated peptide synthesizer (Uppsala, Sweden) by Fmoc‐SPPS on a 0.05 mmol scale using Rink amide resin (ChemPep, 0.51 mmol/g).…”
Section: Methodsmentioning
confidence: 99%
“…48 The trefoil factor family comprises TFF1, TFF2 and TFF3 (also called ITF) that are abundantly secreted in the gastrointestinal tract where they regulate gut homeostasis by promoting gut protection and repair. 49 ITF is highly expressed in the gastrointestinal mucosa, where it protects, maintains, and repairs the gastrointestinal tract, and promotes epithelial restitution, wound healing, increases mucus viscosity and structural integrity of the mucus layer. 50 The present study showed that L. paracasei increased the goblet cells and ITF, and E. coli reduced the content of ITF, making it difficult to repair the intestinal tract.…”
Section: Papermentioning
confidence: 99%